2022
DOI: 10.3390/app12052335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wood Properties and Building Construction on Energy Demand, Thermal Comfort and Start-Up Lag Time of Radiant Floor Heating Systems

Abstract: Radiant floor heating is becoming increasingly popular in cold climates because it delivers higher comfort levels more efficiently than conventional systems. Wood is one of the surface coverings most frequently used in radiant flooring, despite the widely held belief that in terms of thermal performance it is no match for higher conductivity materials if a high energy performance is intended. Given that the highest admissible thermal resistance for flooring finishes or coverings is generally accepted to be 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…The same authors [26], in an experimental analysis under laboratory conditions of four types of wood flooring based on heating start-up and shutdown cycles, reported that wood flooring maintained a high temperature for longer periods once the heating source was removed. Similar results were found in the previous study by the present authors [29], where they analysed the thermal performance of 60 radiant wooden floors for the climate of Madrid and 216 dwellings. In many situations, wooden flooring with high thermal resistance was found to deliver higher comfort levels at a slightly lower energy demand than granite floors.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The same authors [26], in an experimental analysis under laboratory conditions of four types of wood flooring based on heating start-up and shutdown cycles, reported that wood flooring maintained a high temperature for longer periods once the heating source was removed. Similar results were found in the previous study by the present authors [29], where they analysed the thermal performance of 60 radiant wooden floors for the climate of Madrid and 216 dwellings. In many situations, wooden flooring with high thermal resistance was found to deliver higher comfort levels at a slightly lower energy demand than granite floors.…”
Section: Introductionsupporting
confidence: 91%
“…This article enlarges the study performed in the previous research by Ruiz-Pardo et al [29] by extending its scope from dwellings in Madrid, Spain, to include others in 28 cities in which there is a high likelihood of using the heating systems selected according to the Köppen-Geiger classification. The aim was to evaluate the possible effect of the thermal properties of wood, in combination with building characteristics and climate, on the thermal performance of radiant wooden flooring, and to compare it with a highly conductive natural stone floor.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Wooden heating floors have become a widely adopted indoor heating approach because they offer the advantages of comfort, space saving, partition heating, and uniform temperature distribution. [1][2][3] Electric heating elements, including heating cables, [4] hot water pipes, [5] and electrothermal films, [6] are essential parts of the wooden heating floor systems. Scalable, flexible, and film-like carbon fiber paper has a heating temperature range of 30-250 C and an electric-to-radiant power transfer efficiency of more than 97%, making it promising for the application of electric heating elements.…”
Section: Introductionmentioning
confidence: 99%